Rekonstruksi Kebijakan Penyelesaian Sengketa E- Commerce Melalui Arbitrasi Berbasis Keadilan - Buchari, Akbar Himawan (Jurnal sosial dan sains, 2025)
As a country rich in Natural Resources and Energy Resources, it is not uncommon for many business actors to be interested in investing their capital through business cooperation. One of the problems that is a challenge in the business world is the use of e-commerce. This research method uses secondary data consisting of the 1945 Constitution, the Civil Code, the Information Technology Law, and laws related to data protection for the use of e-commerce as well as several cases used as samples to test whether legal protection can be realized on the applicable regulations. The context of electronic commerce is through arbitration. International e-commerce dispute resolution is possible to be resolved—especially those involving minor disputes—in the right forum, namely with "ODR" which is a practical way to provide consumers with the right remedy, cheap and effective remedy, as well as reduce litigation in foreign countries.